AlCl3-promoted growth of alkylated carbon dots with an enhanced nonlinear optical response. Issue 14 (14th March 2022) - Lu, Dandan; Yin, Keyang; Hou, Shida; Li, Penghui; Zhu, Hongxia; Hao, Jingcheng; Li, Hongguang
Abstract : The CDs has been greatly promoted by AlCl3 . The resulting Al-doped, highly conjugated CDs show an impressively good NLO response with RAS behavior. The third-order β of the CDs-containing composite takes the crown among other CDs-based systems. Abstract : Carbon dots (CDs) have attracted increasing attention due to their wide potential applications. However, the rational design of task-specific CDs is still in its infancy. Specifically, some CDs have shown great potential as a new generation of nonlinear optical (NLO) materials, but to achieve high NLO performance remains a big challenge. Herein, we provide a metal-promoted strategy to improve the third-order nonlinear absorption coefficient ( β ) of CDs. Alkylated CDs doped with aluminium (Al) as well as nitrogen and chloride were facilely obtained by pyrolysis of dodecylamine in o -dichlorobenzene in the presence of anhydrous aluminum chloride (AlCl3 ). Growth of CDs promoted by AlCl3 was confirmed, during which the content of the conjugated fragments significantly increased. This structural evolution, together with the doping of Al, changed the absorption and emission of the CDs. By using the Z -scan technique, the reverse saturable absorption behaviour of the CDs embedded in the polymer matrix was confirmed with a β value of up to 7.0 × 10 −6 m W −1, which took the crown among all the CD-based composite materials reported to date.